Model Peningkatan Kepuasan Pelanggan Berbasis Nilai Khidmah dan Amanah di Toserba Sunan Drajat Petiyin - Biyati Ahwarumi; Anas Alhifni; M. Jefri (JOURNAL OF SHARIA ECONOMICS, 2026)
This study aims to analyze the ideal service improvement model, examine the implementation of Khidmah and Amanah values, and investigate their influence on customer satisfaction at Toserba Sunan Drajat Petiyin. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 50 customers selected using accidental sampling. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The analysis included validity testing, reliability testing, structural model evaluation, and hypothesis testing. The results indicate that all research indicators met the validity and reliability criteria. The values of Khidmah and Amanah have been well implemented in service delivery based on customer perceptions. Hypothesis testing revealed that Amanah had a positive and significant effect on customer satisfaction with a path coefficient of 0.395, a T-statistic of 3.731, and a p-value of 0.000. Meanwhile, Khidmah also had a positive and significant effect on customer satisfaction with a path coefficient of 0.583, a T-statistic of 6.363, and a p-value of 0.000. The R-square value of 0.853 indicates that Amanah and Khidmah jointly explain 85.3% of the variance in customer satisfaction. Furthermore, the effect size analysis shows that Khidmah is the most dominant variable influencing customer satisfaction.